(untitled) (The New Uzbekistan Journal of Medicine, 2025)
This article provides detailed information on allergic reactions and their types, pathogenesis, clinical manifestations, and treatment methods, especially desensitization mechanisms. The immunological basis of allergy, rapid and slow-developing reactions, and the dangerous aspects of anaphylaxis are covered based on scientific literature.